2016
DOI: 10.1111/are.13062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary levels of essential oil ( EO ) extract from bitter lemon ( C itrus limon ) fruit peels on growth, biochemical, haemato‐immunological parameters and disease resistance in Juvenile L abeo victorianus fingerlings challenged with A eromon

Abstract: Essential oils (EOs) are used in the food industry because of their biological activity. We evaluated the effects of administration of essential oil (EO) extracted from bitter lemon (Citrus limon) fruit peels on the growth performance, biochemical, haemato‐immunological parameters and possible disease resistance in fingerlings (4 weeks old) Labeo victorianus challenged with Aeromonas hydrophila. Fish were divided into five groups and fed diets supplemented with C. limon fruit peels EO extract at 1%, 2%, 5% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 56 publications
11
45
0
Order By: Relevance
“…A number of studies reported the usefulness of EOs from different plants in aquaculture diets. These studies have suggested that EOs could improve not only the growth performance but also the health status indicated by blood parameters (Ngugi et al, ; de Souza et al, ). Similar results were observed in the current study in terms of fish growth, feed utilization and blood parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported the usefulness of EOs from different plants in aquaculture diets. These studies have suggested that EOs could improve not only the growth performance but also the health status indicated by blood parameters (Ngugi et al, ; de Souza et al, ). Similar results were observed in the current study in terms of fish growth, feed utilization and blood parameters.…”
Section: Discussionmentioning
confidence: 99%
“…peels are rich in numerous biologically active compounds, such as vitamin C, phenolic acids, pectin and flavonoids (Bocco, Cuvelier, Richard, & Berset, ; Manthey & Grohmann, ; Rafiq et al, ) having potential anti‐allergenic, anti‐atherogenic, anti‐inflammatory, antimicrobial, antioxidant, antithrombotic, cardioprotective and vasodilatory effects (Benavente‐García, Castillo, Marin, Ortuño, & Del Rio, ; Middleton, Kandaswami, & Theoharides, ). Several studies on dietary inclusion effects of citrus meal and citrus by‐products fermented on olive flounder ( Paralichthys olivaceus , Temminck & Schlegel) (Lee et al, ; Seo, Kim, Son, & Lee, ) and red sea bream ( Pagrus major Temminck & Schlegel) (Song, Park, Lee, & Lee, ), citrus ( Citrus unshiu Marcovitch) pomace on abalone ( Haliotis discus discus , Reeve) (Jwa & Yeo, ), C. aurantium Linnaeus oil on silver catfish ( Rhamdia quelen Quoy and Gaimard) (Lopes et al, ) and essential oils extracted from bitter lemon ( C. limon Osbeck) peels on fish ( Labeo victorianus Boulenger) (Ngugi, Oyoo‐Okoth, & Muchiri, ) have been reported. Therefore, CPB seems to have high potential as an alternative source for MA in abalone feed as well.…”
Section: Introductionmentioning
confidence: 99%
“…is the third major Citrus species after orange and mandarin in the world (Miran et al 2016), and it is widely used as fresh, beverages, cook material and preservative for food (González-Molina et al 2010;Ngugi et al 2016). Owe to its tart flavor, lemon is popularly used in beverages, ice creams, desserts, salad dressings, and many meat and vegetable dishes.…”
Section: Introductionmentioning
confidence: 99%